Study of the process fermentation by simplified proteic biomass technology production of had scale down of the bioreactor of an industrial plant - Marín Cárdenas, Alfredo; García Rodríguez, Agustín; Herrera Coello, Nelsy; Gómez Rodríguez, Luis (Centro Azúcar Journal, 2008)
With the objective of study the process of fermentation of an plant of production of proteic biomass, were carried experiences to evaluate the fermentation in bioreactor to scale industrial, where were necessary the operational parameters of fermentation, to develop a study satisfactorily of having climbed descending or inverse, adjusting all the operative technical parameters and achieving a geometric similarity between bioreactor and their prototype and the simulation of the environmental conditions. It were carried lower laboratory conditions experiences, in bioreactor with capacity of volume of work about 2 and 20 liters, developing a comparative study between operations batch and increased batch. The results obtained in the studies to laboratory scale don't differ statistically to the industrial results as for yield and productivity, but were we find significant differences when comparing the results from the fermentations to batch and batch increased among if that corroborate those reached since by other investigators that justify the use of the batch increased in this production type, these overcome the levels of yields obtained with the fermentation to batch categorically. It is also evident the appreciable decrease of the time of operation of 10 at 6 hours with the process to increased batch that they impact in the appreciable increase of the levels of productivity.